Two Novel Antioxidant Nonapeptides from Protein Hydrolysate of Skate (Raja porosa) Muscle - Fa-Yuan Hu; Chang-Feng Chi; Bin Wang; Shang-Gui Deng (Marine Drugs, 2015)
In the current study, the preparation conditions of neutrase hydrolysate (SMH) from skate (Raja porosa) muscle protein were optimized using orthogonal L9(3)4 tests, and R values indicated that pH was the most important factor affecting HO· scavenging activity of SMH. Under the optimum conditions of pH 7.0, enzymolysis temperature 60 °C, enzyme/substrate ratio (E/S) 2%, and enzymolysis time 5 h, EC50 of SMH on HO· was 2.14 ± 0.17 mg/mL. Using ultrafiltration, gel filtration chromatography, and RP-HPLC, two novel antioxidant nonapeptides (SP-A and SP-B) were isolated from SMH and their amino acid sequences were found to be APPTAYAQS (SP-A) and NWDMEKIWD (SP-B) with calculated molecular masses of 904.98 Da and 1236.38 Da, respectively. Both showed strong antioxidant activities. SP-A and SP-B exhibited good scavenging activities on HO· (EC50 0.390 and 0.176 mg/mL), DPPH· (EC50 0.614 and 0.289 mg/mL), and O2−· (EC50 0.215 and 0.132 mg/mL) in a dose-dependent manner. SP-B was also effective against lipid peroxidation in the model system. The aromatic (2Trp), acidic (2Asp and Glu), and basic (Lys) amino acid residues within the sequences of SP-B might account for its pronounced antioxidant activity. The results of this study suggested that protein hydrolysate and peptides from skate muscle might be effective as food additives for retarding lipid peroxidation occurring in foodstuffs.